Adiabatic speedup via zero-energy-change control in a spin system. (6th February 2019) - Zhang, Li-Cheng; Ren, Feng-Hua; Chen, Yi-Fei; He, Run-Hong; Gu, Yong-Jian; Wang, Zhao-Ming
Abstract: Adiabatic evolution is required in performing quantum information processing tasks and adiabatic speedup is often used to avoid decoherence problems for a long evolution time. Here, we add a leakage elimination operator (LEO) Hamiltonian to the evolution and adiabatic speedup can be obtained. LEO Hamiltonians can be realized by a sequence of periodic zero-energy-change pulses. By using the Feshbach partitioning technique, we obtain the exact control parameters to realize adiabatic speedup for different types of pulses. Furthermore, we show that this control scheme is fault-tolerant against pulse strength and pulse frequency for specified thresholds.